2022
DOI: 10.5267/j.uscm.2022.6.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of top management commitment on improving operational performance through green purchasing and green production

Abstract: This research has investigated the impact of top management commitment to enhance operational performance through green purchasing and green production Practices in the manufacturing industry. The study has surveyed 122 from 578 manufacturing companies domiciled in East Java, Indonesia, using a questionnaire designed with a seven-point Likert scale. Data analysis used the partial least square. The result revealed that top management commitment affects green purchasing, green production practices, and operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Te concept of TMC resonates with the Teory of Planned Behavior (TPB), which describes behavior based on an individual's will [65]. When an individual's activity has a goal and purpose, TBP behavioral performance occurs.…”
Section: Moderating Role Of Tmcmentioning
confidence: 99%
See 1 more Smart Citation
“…Te concept of TMC resonates with the Teory of Planned Behavior (TPB), which describes behavior based on an individual's will [65]. When an individual's activity has a goal and purpose, TBP behavioral performance occurs.…”
Section: Moderating Role Of Tmcmentioning
confidence: 99%
“…When an individual's activity has a goal and purpose, TBP behavioral performance occurs. An individual's behavior is the result of a logical cognitive process in which the individual assesses information internally before applying it to its external behavior [65]. From this point of view, it has been said that the knowledge and beliefs of top management afect how organizations use new technologies like big data analytics [66] and that managers' concerns about the environment afect how much green innovation operations afect EP and competitive capabilities [67].…”
Section: Moderating Role Of Tmcmentioning
confidence: 99%
“…However, the behavior of top management is considered an essential element to measure organizational culture (Treviño et al, 1998). The role of top management is very important not just in terms of their responsibility to introduce ethical values in organizational culture but also in terms of their commitment to allocating and deploying required resources for implementing green procurement and green supply chain management (Basana et al, 2022). Scholars pointed out that organizational culture determines how procurement managers account for environmental and social criteria when selecting suppliers (Goebel et al, 2012).…”
Section: Procurementmentioning
confidence: 99%
“…That is, most previous studies did not take into account that the effects of green procurement on companies may not always be direct but rather mediated by other outcomes like operational performance (Song et al, 2017). Several studies have demonstrated that green procurement leads to improved operational performance (Basana et al, 2022;Yang et al, 2022). Carter and Jennings (2004) argued that top and middle managers who possess environmental values can likely play a key role in introducing initiatives linked to sustainability.…”
Section: Procurement Managers' Willingness To Paymentioning
confidence: 99%
See 1 more Smart Citation